Krell V. Henry, audiencia ante la Court of Appeal [of England and Wales, civil division], 11 de agosto de 1903 ([1903] 2 K. B. 740)) - Manin, María Soledad; Garaventa, Carlos Adrían (Lecciones y Ensayos, 2012)